Interstellar, between the physics and El Aleph - Meza-Vélez, Iván (2023)
Science-fiction film Interstellar (2014) explores the possibilities offered by Einstein’s general relativity theory through wormholes, black holes and time dilation with great realism. This work studies all the sequences related to physics, especially the astronauts’ journey through a blackhole. Then, considering modern physics, the plausibility of the physical phenomena presented in the film is analyzed. As the central axis of the study, physics and cinematographic art are intertwined through the film image. It is also demonstrated that the last scenes move away from physical concepts, but as symbolic language they approach Borges’s The Aleph, with which a parallel is drawn. Science and art, realism and fiction are characteristics related to the film that are developed in the present work.